Significance of team-based organizations in business process orientation and effectiveness: an application to service firms in Turkey - Dülger, Ayşe Meral. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
Through an organizational design point of view, this study looks into the extent of understanding about business processes and how these views affect team processes and team effectiveness/performance. In particular, this endeavor examines the relationship between Business Process Orientation (BPO), Team Action Processes, Interpersonal Processes and Team Effectiveness/Performance in service firms operating in Turkey. Hypothesized relationships were investigated with a quantitative study which includes a survey. Data are collected from 368 middle-level team members and team managers who operate in the service industry in İstanbul, İzmir, Ankara, Bursa, Kocaeli, Antalya, Turkey and hypothesized relationships are analyzed with structural equation modeling procedure in AMOS 19. The foremost finding of the study is that Business Process Orientation has a significant relationship with Team Action Processes, Interpersonal Processes and Team Effectiveness/Performance. The results indicate that this relationship is significant only when Business Process Orientation is mediated by Team Action Processes and Interpersonal Processes in predicting Team Effectiveness/Performance. Considering that the relationship between Business Process Orientation and team processes and team effectiveness/performance has not been established before, this finding takes the first step in verifying the existence of this relationship and therefore paves the way for future endeavors.
Keywords: Teams in the workplace -- Turkey.; Organization -- Turkey.; Management -- Turkey.